Exome sequencing of hepatocellular carcinomas identifies new mutational signatures and potential therapeutic targets - Schulze, Kornelius; Imbeaud, Sandrine; Letouzé, Eric; Alexandrov, Ludmil B; Calderaro, Julien; Rebouissou, Sandra; Couchy, Gabrielle; Meiller, Clément; Shinde, Jayendra; Soysouvanh, Frederic; Calatayud, Anna-Line; Pinyol, Roser; et al. (Nature genetics, 2015)
Jessica Zucman-Rossi and colleagues report exome sequences of 243 hepatocellular carcinomas. They identify mutational signatures associated with specific risk factors such as alcohol, tobacco and aflatoxin B1 and find genetic alterations potentially targetable by FDA-approved drugs in 28% of the tumors. Genomic analyses promise to improve tumor characterization to optimize personalized treatment for patients with hepatocellular carcinoma (HCC). Exome sequencing analysis of 243 liver tumors identified mutational signatures associated with specific risk factors, mainly combined alcohol and tobacco consumption and exposure to aflatoxin B 1 . We identified 161 putative driver genes associated with 11 recurrently altered pathways. Associations of mutations defined 3 groups of genes related to risk factors and centered on CTNNB1 (alcohol), TP53 (hepatitis B virus, HBV) and AXIN1 . Analyses according to tumor stage progression identified TERT promoter mutation as an early event, whereas FGF3 , FGF4 , FGF19 or CCND1 amplification and TP53 and CDKN2A alterations appeared at more advanced stages in aggressive tumors. In 28% of the tumors, we identified genetic alterations potentially targetable by US Food and Drug Administration (FDA)–approved drugs. In conclusion, we identified risk factor–specific mutational signatures and defined the extensive landscape of altered genes and pathways in HCC, which will be useful to design clinical trials for targeted therapy.